2019
DOI: 10.1111/ene.14008
|View full text |Cite
|
Sign up to set email alerts
|

COPPADIS‐2015 (COhort of Patients with PArkinson's DIsease in Spain, 2015): an ongoing global Parkinson's disease project about disease progression with more than 1000 subjects included. Results from the baseline evaluation

Abstract: Background and purpose In Parkinson's disease (PD), the course of the disorder is highly variable between patients. Well‐designed, prospective studies for identifying PD progression biomarkers are necessary. Our aim was to show the results of baseline evaluations of an ongoing global PD project, COPPADIS‐2015 (Cohort of Patients with PArkinson's DIsease in Spain, 2015). Methods This was an observational, descriptive, nationwide study (Spain). The recruitment period ended in October 2017. Baseline evaluation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…Previous studies have explored the frequency of NMS and motor complications in PD and our results [4] are aligned with them [7‐9]. Although previous reports demonstrated that approximately 40% of patients with PD who were treated with levodopa for 4–6 years experienced motor complications [10], studies examining wearing‐off more specifically have observed that this is a potentially early phenomenon, affecting 42% of patients with PD with <2.5 years of disease when a screening tool was used (self‐rated 19‐question Wearing‐Off Questionnaire) and 21% according to neurologist assessment [11].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous studies have explored the frequency of NMS and motor complications in PD and our results [4] are aligned with them [7‐9]. Although previous reports demonstrated that approximately 40% of patients with PD who were treated with levodopa for 4–6 years experienced motor complications [10], studies examining wearing‐off more specifically have observed that this is a potentially early phenomenon, affecting 42% of patients with PD with <2.5 years of disease when a screening tool was used (self‐rated 19‐question Wearing‐Off Questionnaire) and 21% according to neurologist assessment [11].…”
Section: Discussionmentioning
confidence: 85%
“…Patients with PD from the COPPADIS cohort [4,5] were included in this study. Methodology can be consulted in https://bmcneurol.biomedcentral.com/articles/10.1186/s12883-016-0548-9 [5].…”
Section: Methodsmentioning
confidence: 99%
“…The presented data correspond to the cross-sectional evaluation at baseline of COPPADIS cohort, nevertheless, the assessment of the ICDs/CBs behaviour over time would be more informative. This issue would be overcome in the future since the follow up of this cohort is on-going and we will obtain the longitudinal data 38 . On the other hand, following the methodology of the study, the UPDRS part II evaluation only included motor items to assess the phenotype (tremor dominant, postural instability and gait disorders or undetermined).…”
Section: Discussionmentioning
confidence: 99%
“…PD patients and controls, who were recruited from January 2016 to November 2017 from 35 centers of Spain from the COPPADIS cohort [ 14 ] and were evaluated again at 2-year follow-up, were included in the study. Methodology about COPPADIS-2015 study can be consulted at (25 February 2016) [ 15 ].…”
Section: Methodsmentioning
confidence: 99%